Relationship between caregiver’s and child’s caries prevalence among disadvantaged African Americans - Reisine S, Tellez M, Willem J, Sohn W, Ismail A. (Journal compilation, 2008)
To assess the relationship between African-American caregivers’ and children’s caries levels adjusting for sociodemographic factors.